Accumulation and Productivity Growth in Industrializing Economies - Peter E. Robertson; John S. Landon-Lane (Rutgers University, Department of Economics, 2003)
Historically, episodes of rapid growth are accompanied by significant structural change. In this paper we therefore aim to quantify the extent to which factor accumulation induces structural change and productivity growth in industrializing economies. To fix ideas we present an extension of Barro, Mankiw and Sala-i-Martin?s (1995) growth model that incorporates two sectors, traditional and modern, and an endogenous wage gap, due to efficiency wages. The model thus draws on ideas of Lewis (1954) and the dual economy literature. We quantify the model using a panel of 78 countries over the post war era. The results show that these labour reallocation effects can increase the effective return to physical capital by around 30% in many countries. We conclude that the productivity gains through labour re-allocation are potentially a significant contributing factor to transitional growth episodes in industrializing countries, and provide some examples.
Keywords: O3; O1; O0; 330; growth; development; convergence; dual economy; productivity; Investition; Produktivität; Strukturwandel; Dualökonomie; Lohnstruktur; Theorie; Entwicklungsländer; Schwellenländer